KOLABORASI PEMERINTAH DAN MASYARAKAT DALAM PENYELENGGARAAN PENDIDIKAN: PENDIDIKAN KHUSUS DI PROVINSI RIAU TAHUN 2015-2016 - T. Anisa Pitri; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The problem background in this study in special education in Riau such as still mini and infrastructure for education, lack of teachers who facilities have proficiency in autstanding educational and parens interest provide education to the children who have special needs. To optimize the special education in the riau, government involves the society to collaborate to increas the special education quality.This study aim to describe the actors in the special education and collaboration of government and study in special education in Riau. Method was used in this study is descriptive method qualitative research. Types of research data are primary and secondary data technique of analysis data that used is quantitative descriptive.The result of study show that the correlation of government in Riau and society in special education at 2015-2016 yet affective. It can be seen from program run in collaboration of government and society still minim. The actors involved in special education in Riau play its role each, but they can not potray optimally. The inhibiting factors of collaboration government and society in fulfil of disable is lack of awareness the parties involved in education. Expected to the government and society can improve functions and role in collaborate in order special education can held good.Keywords:Collaboration, Government-Society, And Special Education